Dental arch form and arch dimensions among a group of Egyptian children and adolescents - Sharaf, Rasha F. (2023)
Patients whose casts fulfilled the previously mentioned inclusion and exclusion criteria were included in the current study, to analyze dental arch dimensions in children and adolescents with normal occlusion in primary, mixed and permanent dentitions as well as detection of the most common forms of dental arches among Egyptian children.